On the creep behavior of carbon/epoxy non-crimp fabric composites - Lorandi, Natália Pagnoncelli; Cioffi, Maria Odila Hilário [UNESP]; Shigue, Carlos; Ornaghi, Heitor Luiz (FapUNIFESP (SciELO), 2018)
The use of composites in structural applications requires the study of specific properties to ensure that these materials are safe and an excellent option to replace some metals, for example. In the present study, vacuum assisted resin transfer molding (VARTM) was used prior to obtain carbon/epoxy noncrimp fabric composites. Dynamic mechanical analysis and creep - by using Findley and Burger's methods - tests were performed aiming to evaluate the viscoelastic properties of the composites, in three different temperatures (30, 60 and 90°C) and static stresses (2, 5 and 10 MPa). The viscoelastic properties were also discussed using Weibull parameters obtained from creep curves. In general, the deformation was temperature and stress dependent, which was corroborated by the viscoelastic parameters obtained from both models.
Keywords: Creep behavior; Dynamic mechanical analysis; Non-crimp fabric (NCF); Viscoelasticity